Low-Cost and High-Efficiency Method for Detecting Vertical Bends of Subsea Pipelines - Guo Lin; Zeng Zhoumo; Huang Xinjing; Li Mingze; Feng Hao; Li Jian; Rui Xiaobo (IEEE Access, 2020)
Subsea pipelines often bend upward due to vertical buckling or downward due to spanning and seabed settling. Typically, harsh environments and the difficulty of accessing underwater pipelines make the inspection and monitoring of subsea pipeline bends a challenging task. This paper demonstrates a low-cost, high-efficiency, and quasi-real-time method for detecting the vertical bends of subsea pipelines by using an in-pipe spherical detector (SD) with rolling features and a low blockage risk. When the SD rolls forward inside a bent pipeline, its rolling speed will change as it moves uphill and downhill, which can be indicated by the centripetal acceleration-the DC component of the recorded rolling acceleration signals. To achieve a high bend detection performance, the mass of the SD should be distributed in a centered disc area to make the SD capable of stably rolling around one of the sensitive axes of the accelerometer, and the accelerometer should be kept as far from the rotation axis as possible. It is experimentally demonstrated that a convex/concave DC component indicates that the pipe is bent downward/upward, and the bend detection resolution can reach 1 cm for a 12 m pipeline.